PENGARUH SHOP ENVIRONMENT, STAFF, INTEGRATED MARKETING COMMUNICATIONS, DAN HEDONIC VALUE TERHADAP IMPULSIVE BUYING PADA KONSUMEN CARREFOUR DI SURABAYA - Laksono, Veronica Lavinia (Kajian Ilmiah Mahasiswa Manajemen, 2013)
This Study analyzes the various factors that influence consumers in Impulsive Buying at Carrefour Surabaya. The purpose of this study was to determine the effect of variables Shop Environment, Staff, Integrated Marketing Communications and Hedonic Value on Impulsive Buying at Carrefour Customer in Surabaya. The Sampling technique used was Purposive Sampling, the technique of determining sample by choosing sample where the population according to the researchers desire. The criteria used are live in Surabaya, aged 17 years and never made a purchase at Carrefour Surabaya. The method used in this study is the method of multiple regression analysis with SPSS 17. The research concludes that there is a significant positive effect on any relationship between variables Shop Environment, Staff, Integrated Marketing Communications and Hedonic Value to variable Impulsive Buying. The conclusion of the studyis that consumers make purchase simpulsively driven by several factors namely Shop Environment, Staff, Integrated Marketing Communications by retailers and Hedonic Value attitude that is within each of them.